(untitled) (Global Journal of Medical Research, 2022)
Human papillomavirus (HPV) infection is the most common sexually transmitted disease globally, affecting mainly women and being responsible for developing oral and cervical cancer. This study aims to determine the presence of HPV and its high and low-risk subtypes in women who submitted to the HPV genotyping test. One hundred thirteen vaginal secretion samples were collected from August 2018 to August 2019 from women aged between 17 to 78 years. The material was analyzed for HPV genotyping using a Flow chip methodology, 39 samples were identified positive for the HPV virus, while 74 samples did not present the virus. No relation between HPV infection and age could be established. Considering the groups, it was possible to identify two peaks of infection, one occurring in the class between 16 to 25 years and another in between 46 -55. This result was not expected since the second class’s age is not considered a high risk for HPV.